Implementing a portafolio-based writing assessment in the level four at the Pontificia Universidad Católica del Ecuador Sede Ambato - Aguilar Vásconez, Wilson Daniel (2007)
1. The writing skill. 2. Portafolio-Based writing assesment. 3. Applying language learning strategies to the writing skill. 4. Methodology and research. 5. Data analysis. 6. Conclusions and recommendations